Factors associated with pericardial effusion in pediatric systemic lupus erythematosus - Pediana Rachmawati; Indah K. Murni; Sasmito Nugroho; Noormanto Noormanto; Sumadiono Sumadiono (Indonesian Pediatric Society, 2018)
Background Cardiovascular involvement in systemic lupus erythematosus (SLE) has been reported to range from 4-78%. Complications can affect all structures of the heart, including the endocardium, myocardium, pericardium, and valves. Pericarditis is the most common manifestation, with an incidence of 11-54% in SLE patients. Pericardial effusion is often observed in patients with pericarditis, and can be confirmed by echocardiography. Objective To determine factors associated with pericardial effusion in children with SLE. Methods We conducted a restrospective cross-sectional study by reviewing medical records of children with SLE aged less than 18 years who underwent echocardiography at the Dr. Sardjito Hospital. Yogyakarta, from January 2011 to March 2018. Patients with congenital heart disease or incomplete medical records were excluded. A multivariate logistic regression analysis was done to determine factors that independetly associated with pericardial effusion. Results Among 165 children with SLE, 73 fulfilled the inclusion criteria. The prevalence of pericardial effusion was 54.8%. Median age was 13 (range 5-17) years and the female-to-male ratio was 8:1. Hemolytic anemia (OR=4.135; 95%CI 1.039 to 16.453; P=0.044) was significantly associated with pericardial effusion. Conclusion Hemolytic anemia is significantly associated with pericardial effusion in children with SLE.